Direct cost of cochlear implants in Germany: A strategic simulation - Christin Thum; Thomas Lenarz; Steffen Fleßa (Health Economics Review, 2022)
Background: Despite the current undersupply of cochlear implants (CIs) with simultaneously increasing indication, CI implantation numbers in Germany still are at a relatively low level. Methods: As there are hardly any solid forecasts available in the literature, we develop a System Dynamics model that forecasts the number and costs of CI implantations in adults for 40 years from a social health insurance (SHI) perspective. Results: CI demand will grow marginally by demographic changes causing average annual costs of about 538 million exteuro. Medical-technical progress with following relaxed indication criteria and patients' increasing willingness for implantation will increase implantation numbers signifcantly with average annual costs of 765 million exteuro. Conclusion: CI demand by adults will increase in the future, thus will the costs for CI supply. Continuous research and development in CI technology and supply is crucial to ensure long-term fnancing of the growing CI demand through cost-reducing innovations.
Keywords: 330; Cochlear implant; Simulation; System dynamics; Health insurance; Cost